Using projective assessment techniques in career counselling - Amundson, Norman E. (Canadian Journal of Counselling and Psychotherapy, 2012)
It is the purpose of this article to explore ways in which projective assessment can be more effectively integrated into career counselling. The author introduces new types of career projective techniques and suggests that the emphasis should be on using these methods as a means of conducting structured counselling interviews. The adoption of this viewpoint has implications for the continued development of projective assessment and for the training of counsellors.